Nivel de precios y actividad económica: Un ensayo económico en el virreinato del Perú (siglos XVI-XVII) - Noejovich, Héctor Omar (Economia, 2000)
This essay deals with some basic economic variables: prices, coinage and economic activity level. The data have been taken from published and well known sources and developed as chronological series. So, analyzing trends and tluctuations, we got a suitable picture of Peru viceroyalty’s economy from Lima and Potosi, during the 16th and 17th centuries. It also introduces an special technique for estimating economic activity level.